The effect of single and repeated bouts of prolonged cycling and circadian variation on saliva flow rate, immunoglobulin A and a-amylase responses - Li, T.-L.; Gleeson, M. (Journal of Sports Sciences, 2004)
The purpose of this study was to establish the effect of exercise at different times of day on saliva flow rate, immunoglobulin A (sIgA) concentration and secretion rate, and α-amylase activity, and to establish how these parameters change following a second exercise bout performed on the same day. In a counterbalanced design, eight male volunteers participated in three experimental trials separated by at least 4 days. On the trial with afternoon exercise only, the participants cycled for 2 h at 60% &Vdoti;O2max starting at 14:00 h. On the other two trials, participants performed either two bouts of exercise at 60% &Vdoti;O2max for 2 h (the first started at 09:00 h and the second started at 14:00 h) or a separate resting trial. Unstimulated saliva samples were obtained 10 min before exercise, after 58 - 60 min and during the last 2 min of exercise, and at 1 h and 2 h after exercise. Venous blood samples were taken 5 min before exercise and immediately after exercise for both bouts. Participants remained fasted between 23:00 h on the day before the trials and 18:00 h on the day of the trial. Circadian variations were found in sIgA concentration, which decreased with time from its highest value in the early morning to its lowest value in the evening, and salivary α-amylase secretion rate, which increased from its lowest value in the morning to its highest value in the late afternoon. Cycling at 60% &Vdoti;O2max for 2 h significantly decreased saliva flow rate, increased sIgA concentration and α-amylase activity, but did not influence sIgA secretion rate. Performing prolonged cycling at different times of day did not differentially affect the salivary and plasma hormonal responses in the short term. Performance of a second prolonged exercise bout elicited a greater plasma stress hormone response but did not appear to compromise oral immunity acutely. These findings also suggest that, in terms of saliva secretion, sIgA and α-amylase responses, a 3 h rest is enough to recover from previous strenuous exercise. During such exercise, sympathetic stimulation appears to be strong enough to inhibit saliva flow rate; however, it appears that it does not increase sIgA output via transcytosis.